Differential Effects on Intestinal Adaptation Following Exogenous Glucagon-Like Peptide 2 Therapy With and Without Enteral Nutrition in Neonatal Short Bowel Syndrome. (February 2017) - Lim, David W.; Diané, Abdoulaye; Muto, Mitsuru; Vine, Donna F.; Nation, Patrick N.; Wizzard, Pamela R.; Sigalet, David L.; Bigam, David L.; Pencharz, Paul B.; Turner, Justine M.; Wales, Paul W.
Background: We aim to study the efficacy of exogenously administered glucagon-like peptide 2 (GLP-2) on intestinal adaptation in 2 preclinical models of neonatal short bowel syndrome (SBS) according to remnant intestinal anatomy, with and without ileum. Furthermore, we aim to determine if this adaptive effect was potentiated with enteral nutrition (EN). Methods: Neonatal piglets were block-randomized to 75% mid-intestinal (JI group, retains ileum) or distal-intestinal (JC group, has no ileum) resection or no resection (sham control) and GLP-2 treatment (11 nmol/kg/d) or saline control for 7 days. Piglets received nutrition support, either 100% parenteral nutrition (PN; 0% EN, n = 32 in total) or 80% PN + 40% EN (n = 28 in total). Adaptation was assessed by morphological and histological changes, as well as RT quantitative polymerase chain reaction of nutrient transporters and tight junctional proteins and fat absorption. Data are analyzed by 3-way analysis of variance (ANOVA) and 2-way ANOVA per EN level. Results: GLP-2 treatment lengthened villi, deepened crypts, and improved intestinal weight in the remnant intestine of JC piglets. EN was a more potent adaptive stimulus for JI piglets. Small intestinal lengthening occurred only in the JI group, when given EN. There was no difference in total fat absorption and messenger RNA expression of nutrient transporters and tight junctional proteins. Conclusions: GLP-2 administration augmented structural adaptation in JC piglets with distal intestinal resection. Given JI anatomy, further stimulation by GLP-2 treatment over innate adaptation and stimulation by EN was modest and restricted to ileum. The differential effect of GLP-2 in neonatal SBS, depending on remnant anatomy, has important implications for clinical translation and planning of clinical trials.